2018
DOI: 10.3727/096504017x15105708598531
|View full text |Cite
|
Sign up to set email alerts
|

The Long Noncoding RNA HOTAIR Promotes Colorectal Cancer Progression by Sponging miR-197

Abstract: The long noncoding RNA HOX transcript antisense RNA (HOTAIR) has been found to be overexpressed in many human malignancies and involved in tumor progression and metastasis. Although the downstream target through which HOTAIR modulates tumor metastasis is not well known, evidence suggests that microRNA-197 (miR-197) might be involved in this event. In the present study, the significance of HOTAIR and miR-197 in the progression of colorectal cancer was detected in vitro and in vivo. We found that HOTAIR expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 34 publications
(18 reference statements)
4
25
0
Order By: Relevance
“…For example, it has been reported that HOTAIR can mediate CRC tumorigenesis and liver metastasis in vivo (26). Furthermore, HOTAIR could promote CRC cell proliferation, migration, and invasion via sponging miR-197 (27). Consistent with a previous study, high HOTAIR expression indicates poor prognosis for patients with CRC metastasis (28).…”
Section: Discussionsupporting
confidence: 72%
“…For example, it has been reported that HOTAIR can mediate CRC tumorigenesis and liver metastasis in vivo (26). Furthermore, HOTAIR could promote CRC cell proliferation, migration, and invasion via sponging miR-197 (27). Consistent with a previous study, high HOTAIR expression indicates poor prognosis for patients with CRC metastasis (28).…”
Section: Discussionsupporting
confidence: 72%
“…The elevated expression of Hotair was observed in multiple cancer types, [16][17][18] and our results also demonstrated that it was significantly upregulated in a panel of CRC cells ( Figure 1A). In 20 paired CRC clinical specimens, the expression of Hotair was increased in CRC tissues when compared with their adjacent nontumor tissues ( Figure 1B).…”
Section: Hotair Was Significantly Upregulated In Crc Cells and Clinsupporting
confidence: 76%
“…The abnormal expression of lncRNA plays an important role in cancer progression. Recently, large amount of researches have demonstrated that many lncRNAs such as HOTAIR, and metastasis associated lung adenocarcinoma transcript 1 (MALAT1) are highly expressed in colorectal cancer, breast cancer, hepatocellular carcinoma and some other cancer tissues and are closely related to a variety of cancer metastasis, thus can be used as targets for cancer early diagnosis, treatment and prognosis prediction [17,18]. CCAT2, as a novel oncogene, is located in the hotspot of tumour-related rs6983267 SNP, which promotes the occurrence and development of kinds of cancers by affecting Wnt and TGF-b signalling pathways [9,19].…”
Section: Discussionmentioning
confidence: 99%